2006
DOI: 10.1002/ffej.20078
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of uranium‐contaminated waters using organic‐based permeable reactive barriers

Abstract: A literature review and screening study suggest the feasibility of using lowcost organic materials within a permeable reactive barrier (PRB)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…The PRBs contain a zone of reactive material that is designed to act as an in situ treatment zone for specific contaminants as groundwater flows through it [248][249][250]. The feasibility of using low-cost organic materials within a permeable reactive barrier to treat uranium contaminated environmental components was also investigated, because a permeable reactive barrier is considered an innovative, green engineering approach used for soil and groundwater remediation.…”
Section: Permeable Reactive Barriers (Prbs)mentioning
confidence: 99%
See 4 more Smart Citations
“…The PRBs contain a zone of reactive material that is designed to act as an in situ treatment zone for specific contaminants as groundwater flows through it [248][249][250]. The feasibility of using low-cost organic materials within a permeable reactive barrier to treat uranium contaminated environmental components was also investigated, because a permeable reactive barrier is considered an innovative, green engineering approach used for soil and groundwater remediation.…”
Section: Permeable Reactive Barriers (Prbs)mentioning
confidence: 99%
“…The feasibility of using low-cost organic materials within a permeable reactive barrier to treat uranium contaminated environmental components was also investigated, because a permeable reactive barrier is considered an innovative, green engineering approach used for soil and groundwater remediation. The results showed that it has a high potential to threat shallow aquifer at a lower cost than pump-and-treat methods, but its cost-effectiveness has not yet been proven, due to a lack of long-term data [249][250][251][252][253]. Schad and Gratwohl [253] have calculated that the cost of remediation using PRB is 50% less than the pump-and-treat technique, while human exposure is reduced.…”
Section: Permeable Reactive Barriers (Prbs)mentioning
confidence: 99%
See 3 more Smart Citations